MITIGATION EFFORTS AND STRATEGIES FOR MANAGING HUMAN-ELEPHANT CONFLICT IN BUKIT BARISAN SELATAN NATIONAL PARK, INDONESIA - Gumay Febryano, Indra; Pratiwi, Popy; Iswandaru, Dian; Hilmanto, Rudi (Jurnal Belantara, 2024)
This study aims to determine the conflict mitigation efforts that have been carried out and analyze strategies for managing human-elephant conflicts in the Bukit Barisan Selatan National Park. The research data was collected by focus group discussion and observation. The collected data were analyzed descriptively based on the factors of strength, weakness, opportunity and threat analysis to determine the strategy for managing human-elephant conflict. The results of the study indicate that several efforts have been made to reduce the incidence of conflict through patrols, monitoring, and dispelling and escorting using firecrackers. The strategy supports an aggressive growth policy (growth oriented strategy). It is hoped that the incidence of human-elephant conflict can be reduced or suppressed through a holistic and integrative approach. Mitigation of human conflict with elephants that can be done in the long term is by making special interest tourism programs and increasing human resource capacity. Keywords: conflict, conflict management, elephant, mitigation strategy